2018
DOI: 10.1111/imcb.12053
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐specific Helios, Neuropilin‐1 Tregs induce apoptosis of autoreactive B cells via PD‐L1

Abstract: Regulatory T cells (Tregs) maintain self-tolerance and prevent autoimmunity by controlling autoreactive T cells. We recently demonstrated in vivo that Tregs can directly suppress auto-reactive B cells via programmed death ligand 1 (PD-L1) that ligated PD-1 on B cells and caused them to undergo apoptosis. Here, we asked whether this mechanism is utilized by thymus-derived natural Tregs and/or by peripheral lymphoid tissue-induced Tregs. We first demonstrated that antigen-specific PD-L1-expressing Tregs were ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In order to isolate Tregs more precisely, molecules that could be linked only in this subset of cells have been searched for many years. For example, high expression of Helios and Neuropilin-1 has been recently described as the intracellular markers of nTregs which may also be helpful [ 50 ]. nTregs are produced from CD4 + thymocytes by a stimulation of the TCR receptor with autoantigens [ 51 , 52 ].…”
Section: Subpopulation Of Tregs and Their Origin ( Figure 1mentioning
confidence: 99%
“…In order to isolate Tregs more precisely, molecules that could be linked only in this subset of cells have been searched for many years. For example, high expression of Helios and Neuropilin-1 has been recently described as the intracellular markers of nTregs which may also be helpful [ 50 ]. nTregs are produced from CD4 + thymocytes by a stimulation of the TCR receptor with autoantigens [ 51 , 52 ].…”
Section: Subpopulation Of Tregs and Their Origin ( Figure 1mentioning
confidence: 99%
“…According to molecular markers, Tregs fall into two major categories: resting/naïve Treg (rTreg, FOXP3 lo CD45RA + CD25 lo ) and effector/activated Treg (eTreg, FOXP3 hi CD45RA − CD25 hi ) (Ohue and Nishikawa, 2019). Effector/activated Treg has a strong immunosuppressive function and inhibits anti-tumor immunity through various molecular mechanisms, such as the regulation of the immune checkpoint molecules (Kamada et al, 2019), induction of apoptosis for immune effector cells (Gotot et al, 2018), and production of immunosuppressive cytokines (Collison et al, 2007). It has been reported that inhibition of Nr4a suppresses tumor progression via weakening Treg-mediated immune tolerance (Hibino et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, mouse Treg lacking PD-1 were shown to be activated and have high suppressive potential ( 156 ), which underlines the necessity for further studies of this axis in human Treg. Additionally, human CD4 + Treg express PD-L1 in response to IL-7 ( 154 ) and induce apoptosis in PD-1 + Tconv ( 157 ) and autoreactive B-cells ( 158 ). As CTLA-4 has an important role in Treg function and increased degradation of CTLA-4 as present in LRBA deficiency is associated with high levels of Treg apoptosis, stabilizing strategies for sustained or increased CTLA-4 expression may also improve human Treg survival ( 159 , 160 ).…”
Section: Genetic Engineering Strategies For Increased Proliferation Amentioning
confidence: 99%